2021
DOI: 10.3390/joitmc7030188
|View full text |Cite
|
Sign up to set email alerts
|

User Innovativeness and Fintech Adoption in Indonesia

Abstract: The integration of the financial industry and financial technology (Fintech) plays a pivotal role in increasing financial services reach and inclusion for the large unbanked population in Indonesia. Fintech adoption optimization expands the financial access to formal financial institutions, especially to vulnerable groups such as the unbanked population who predominantly reside in rural areas far from formal financial institutions. Fintech is viewed as a game changer to bring finance to the unreached communiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
67
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 117 publications
(125 citation statements)
references
References 58 publications
7
67
0
5
Order By: Relevance
“…The perception that fintech services provide satisfaction when conducting financial transactions motivates fintech service users to adopt financial technologies. Recent studies by Rahman et al (2021) and Setiawan et al (2021) agree similarly that user attitude impacts financial technology adoption positively.…”
Section: Resultsmentioning
confidence: 76%
See 1 more Smart Citation
“…The perception that fintech services provide satisfaction when conducting financial transactions motivates fintech service users to adopt financial technologies. Recent studies by Rahman et al (2021) and Setiawan et al (2021) agree similarly that user attitude impacts financial technology adoption positively.…”
Section: Resultsmentioning
confidence: 76%
“…Personal innovativeness to new technologies is essential in improving experiences and creativity, including technology adoption. A recent study by Twum et al (2021) and Setiawan et al (2021) also found that user innovativeness influences fintech adoption both directly and indirectly.…”
Section: Resultsmentioning
confidence: 91%
“…This postulate has been supported by Khan, K. A. et al [10] that generations and sex have the key impact on the rate of technological adoption. On the other side previous studies e.g., Laywilla et al [8] highlighted the Unified Theory of Acceptance and use of technology (UTAUT) as the source to use Fin-Tech applications. Similar has been indicated by Hill, Binni, and Huang et al [4] .…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…Therefore, there is a need to explore the relationship between financial literacy and use of financial technology. However, previous studies also indicated that adoption of Fin-Tech was actually caused due to the technological orientation, Setiawan, B. et al [8] . Therefore, the two-fold purpose of this study is also to explore the base of relationship that either it is based on financial literacy or based on technological orientation.…”
Section: Statement Of Problemmentioning
confidence: 99%
See 1 more Smart Citation